Doctors’ Knowledge and Practice toward Evidence-Based Medicine in Benghazi Teaching Hospitals - T. Elsherif, Alsanussi; A. Kashbour, Alhassan; N. Elshaari, Nabil; R. Farkash, Fatma; M. Ali, Marwa; E. Bozrida, Hisham; A. Elgaddafi, Mohammed; Elqutrani, Esraa; Elseliny, Hadeer; Houla, Ramadan; M. Elbarasi, Mahmoud (Benghazi University Medical Journal, 2025)
Background: Evidence-based medicine (EBM) is the utilization of the best evidence available from reliable, bias-free clinical trials and the integration of that evidence with the preferences and conditions of the patient. The current study intends to comprehensively evaluate the status of EBM knowledge, attitude, and practice among doctors in Benghazi teaching hospitals because there have been no studies conducted in this field in Benghazi, Libya. Methods: This cross-sectional study was conducted in August 2023. 129 doctors from teaching hospitals in Benghazi representing a variety of specialties, including medicine, pediatrics, surgery, obstetrics and gynecology (OBGYN), and others, participated in the study. A valid questionnaire that could be self-administered served as the data collection tool. Cronbach’s alpha was used to evaluate the questionnaire’s internal consistency. Results: The study showed that 64.3% of the participated doctors had heard of EBM. The overall level of knowledge was relatively low. In general medicine doctors demonstrated more knowledge about EBM than other specialties, and more aware of the term of EBM than the other participants. Medicine specialty doctors had the highest score in knowledge, whereas paediatricians had the lowest score. Pediatricians were less likely to hear of the term EBM compared to medicine doctors, odds ratio: 3.83 (95% CI, 1.45 – 10.11), p-value: 0.007, and had less knowledge about EBM, p-value of 0.037. Conclusion: The study indicates that while most participants have a positive attitude towards EBM, they have limited understanding. To improve EBM practice and accessibility, an electronic library with online databases should be established, and EBM training programs should be included in undergraduate and postgraduate curricula.